1975
DOI: 10.1088/0022-3727/8/5/011
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency effective mass of charge carriers in n-CdS

Abstract: The free-carrier effective mass is estimated from the measurement of the microwave Faraday effect in n-CdS at liquid nitrogen temperature. The experiment is performed using the straight-through transmission technique at 24 GHz. A theoretical computation of the Faraday rotation is made by the theory of Donovan and Webster (1963) and compared with the experimental value for the combination of the different scattering mechanisms namely piezoelectric potential, deformation potential, and polar optical phonon scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Higher activation energy for the decomposition of blends led to better thermal stability. This fact has been evidenced by various workers in the past [33][34][35][36][37] for different systems.…”
Section: àE/rtmentioning
confidence: 63%
“…Higher activation energy for the decomposition of blends led to better thermal stability. This fact has been evidenced by various workers in the past [33][34][35][36][37] for different systems.…”
Section: àE/rtmentioning
confidence: 63%
“…It could also be seen from Figure 12 that the film surface were strongly affected by solvents like methanol, acetone, and MEK whereas the films retained their surface in solvents like tolune, xylene, and MTO for a period of 12, 9, and 10 months, respectively. This behavior might be attributed to the fact that the resole, prepared from p ‐cresol offered greater reactivity as compared to phenol and o ‐cresol resulting in a more complex structure to provide these resistance as compared to other resoles and might result greater degree of crosslinking also affected the same 13, 14…”
Section: Resultsmentioning
confidence: 99%
“…These blend systems are used in electronic industries as molding and sealing compounds for electronic packaging, protective coatings, composites, and many other application areas such as aerospace, marine, and satellite communications. The use of proper curing agents can convert such resins into a void‐free highly crosslinked network, which ultimately can affect the thermal stability of the blend systems 11–14. By changing the type of phenol, in the resole, may also affect the properties of the blend systems.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the first papers (Rosenberg et al, 1964) it was shown that the Faraday rotation can be resonantly enhanced by a FabryPerot resonator. The importance of considering the effects of internal multiple reflections in the measurements of the Faraday rotation angle was noted by the authors (Piller 1966;Rheinhlander et al, 1975;Stramska et al 1968;Srivastava et al, 1975;Vorobev et al, 1972).…”
Section: Introductionmentioning
confidence: 99%